ANALISIS EFEKTIVITAS, KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN PADA PENDAPATAN ASLI DAERAH (PAD) KABUPTEN SLEMAN (Studi kasus pada Dinas Pendapatan Asli Daerah Kabupaten Sleman Tahun Anggaran 2011-2016) - Yohanis Baru; Sri Ayem; Sunarto Sunarto (JURNAL EKOBIS DEWANTARA, 2018)
Regional Revenue (PAD) also contributes significantly to the Sleman District Budget, with an average increase of 30.54% per annum over the last five years (2011-2015). This shows the financial capacity of the local government of Sleman Regency is quite capable. Meanwhile, the comparison between the target and realized revenues from PAD during the same period showed substantial increases. The components of PAD in Sleman Regency are numerous. Sleman Regency is interesting to be examined by the author is the tax Hotel and Restaurant. This type of research is quantitative research. Variables in this study are regional income, hotel and restaurant tax. Data completion technique is done by documentation. Data obtained from the Regional Financial Management and Finance Office of Sleman Regency in the financial statements Sleman District Government of 2011 to 2016. The analysis used is an effective analysis and contribution analysis. The results showed: (1) The average rate of hotel reception in Sleman Regency in 2011-2016 amounted to 114.81 (very effective), the average acceptance rate of restaurants in Sleman in 2011-2016 amounted to 119.99 is very effective) , (3) The average rate of hotel revenues and restaurant taxes in Sleman District in 2011-2016 amounted to 116.73 (very effective), (4). The average contribution of tax revenues to indigenous peoples (PAD) of Sleman Regency in 2011-2016 is 9,33% or strongly donated (SB), (5) Contribution of average of acceptance of restaurant to indigenous community (PAD) Sleman Regency in 2011- 2016 of 5.69% or very (PAD) of Sleman Regency in 2011-2016 of 15.01% or strongly donated (SB).